Manajemen Pendidikan Pembelajaran Daring Dalam Situasi Pandemi - Sa'diyah, Rika; Kurniawan, Kurniawan; Ali, Mukti; Irawan, Imam (LPPM Universitas Mohammad Husni Thamrin, 2022)
Online learning is an online or face-to-face learning system, using the internet network, with the help of media such as laptops, computers and smartphones. This Learning System is one of the learning options carried out during and after the Covid-19 pandemic. So that it becomes a concern for all of us, including student groups. One of the efforts to find out the effectiveness of online learning is by doing research. The purpose of this study is to analyze the effectiveness of implementing online learning for students. The method we use is descriptive method, namely using data collection techniques by surveying via Google form. The samples used in this study were 78 students. The results of this study indicate that online learning is quite effective, because there are still many obstacles faced so that learning is not in accordance with its achievements. The conclusion from this study is that in the future online learning must be improved with better and more varied learning media.